1971
DOI: 10.1677/joe.0.0510735
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gastrin as a Calcitonin Secretagogue

Abstract: SUMMARY Our earlier observation that pentagastrin is a calcitonin (CT) secretagogue was confirmed and extended to include both synthetic human gastrin I and pure porcine gastrin II. The latter hormone was shown to stimulate the secretion rate of CT from thyroid preparations perfused in situ in anaesthetized pigs at concentrations (0·5 nmol/l) similar to those found after stimulation of gastrin production by a meat extract placed in the stomach (0·2 nmol/1). These concentrations of plasma gastrin are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1975
1975
1989
1989

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…This, together with the finding of calcitonin release by endogenous gastrin in young pigs [3], lead to propose the existence of an entero-thyroid axis, which may play a role in the fine regulation of Ca [36]. As after HSV also in the rat serum gastrin is elevated [ 14], it was speculated by us in the present work that this factor may lead to a disturbance of the postulated entero-thyroidal axis and secondarily to modifications of Ca metabolism in analogy to the spectrum of changes observed after HSV in man [23,29].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…This, together with the finding of calcitonin release by endogenous gastrin in young pigs [3], lead to propose the existence of an entero-thyroid axis, which may play a role in the fine regulation of Ca [36]. As after HSV also in the rat serum gastrin is elevated [ 14], it was speculated by us in the present work that this factor may lead to a disturbance of the postulated entero-thyroidal axis and secondarily to modifications of Ca metabolism in analogy to the spectrum of changes observed after HSV in man [23,29].…”
Section: Discussionsupporting
confidence: 57%
“…Gastrin and pentagastrin are well known to stimulate calcitonin [3,4,6,17,22,36,37] and parathyroid hormone [18,37]. Furthermore, in the Zollinger-Ellison syndrome hypergastrinemia is associated with higher calcitonin [32], and in rats after exclusion of the antrum and subsequent hypergastrinemia a hyperplasia of the parathyroid glands had been reported [13].…”
mentioning
confidence: 99%
“…In pharmacologic doses pentagastrin is a well-known CT secretagogue (1)(2)(3)(4), and many studies suggest that endogenous gastrin levels could play a major role in regulating CT secretion (5,10). We have demonstrated that in normal young men, ingestion of Ca resulted in dose-related increases of circulating Ca, iG, and iCT concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacologic doses of calcium and gastrin are known to be calcitonin (CT)' secretagogues in normal man (1), and animal studies (2,3) suggest that gastrin might be a major physiologic regulator of CT secretion. However, a recent study from this laboratory (4) showed that mixed meals, which markedly stimulated gastrin secretion but did not raise serum calcium levels, had no effect on plasma immunoreactive CT (iCT) concentrations in normal men.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium increases the effect of gastrin and pentagastrin [54,55], adding to the sensitivity of acid secretion [56], Before starting on dialysis the patients are, as a rule, hypocalcémie, which may re sult in a decreased response of gastrin on the parietal-cell receptors. Both dialysis and transplantation raise the serum level of cal cium, which might explain the increased sen sitivity of acid secretion [48].…”
Section: Role O F Gastric Secretionmentioning
confidence: 99%